2013
DOI: 10.1186/1471-2407-13-99
|View full text |Cite
|
Sign up to set email alerts
|

The expression level of miR-18b in hepatocellular carcinoma is associated with the grade of malignancy and prognosis

Abstract: BackgroundMany studies support the hypothesis that specific microRNA (miRNA) expression in various human cancers including hepatocarcinogenesis is closely associated with diagnosis and prognosis. In hepatocellular carcinoma (HCC), malignancy level is related to the degree of histological differentiation.MethodsIn order to establish a novel biomarker that can determine the degree of malignancy and forecast patient prognosis, we performed a microarray analysis to investigate the miRNA expression profiles in 110 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…miR-18b plays an oncogenic or tumor suppressive role in different cancer types (17). For instance, miR-18b is upregulated in HCC, and higher miR-18b level predicates poor prognosis (18). Moreover, overexpression of miR-18b increased HCC cell proliferation, while inhibited cell adhesion ability, indicating that miR-18b acts as an oncogene in HCC (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-18b plays an oncogenic or tumor suppressive role in different cancer types (17). For instance, miR-18b is upregulated in HCC, and higher miR-18b level predicates poor prognosis (18). Moreover, overexpression of miR-18b increased HCC cell proliferation, while inhibited cell adhesion ability, indicating that miR-18b acts as an oncogene in HCC (18).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-18b is upregulated in HCC, and higher miR-18b level predicates poor prognosis (18). Moreover, overexpression of miR-18b increased HCC cell proliferation, while inhibited cell adhesion ability, indicating that miR-18b acts as an oncogene in HCC (18). On the contrary, miR-18b was recently reported to inhibit MM (19).…”
Section: Introductionmentioning
confidence: 99%
“…A number of miRNAs have been revealed to be involved in the pathogenesis of HCC (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The roles of miR-1271 in numerous types of cancers have previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-18b was highly expressed in breast cancer and modulated gene expression levels involved in cell migration (22). The expression level of miR-18b in hepatocellular carcinoma was associated with the grade of malignancy and prognosis (26). The results of the present study have revealed that miR-18b was significantly upregulated and promoted human OC cell migration and invasion.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have demonstrated that the aberrant expression level of miR-18b may be present in diverse human pathologies, including multiple sclerosis, cardiac hypertrophy and chronic hepatitis B virus infection (22,23). miR-18b has attracted much attention as it is frequently upregulated and acts as a oncogene in human gastric cancer (24), colonic cancer (25), breast cancer (22) and hepatocellular carcinoma (26). However, whether miR-18b is involved in the development and progression of OC remains unclear.…”
Section: Introductionmentioning
confidence: 99%